MiR-16 mediates trastuzumab and lapatinib response in ErbB-2-positive breast and gastric cancer via its novel targets CCNJ and FUBP1 - Venturutti, Leandro (2016)
ErbB-2 amplification/overexpression accounts for an aggressive breast cancer (BC) subtype (ErbB-2-positive). Enhanced ErbB-2expression was also found in gastric cancer (GC) and has been correlated with poor clinical outcome. The ErbB-2-targeted therapiestrastuzumab (TZ), a monoclonal antibody, and lapatinib, a tyrosine kinase inhibitor, have proved highly beneficial. However,resistance to such therapies remains a major clinical challenge. We here revealed a novel mechanism underlying theantiproliferative effects of both agents in ErbB-2-positive BC and GC. TZ and lapatinib ability to block extracellular signal-regulatedkinases 1/2 and phosphatidylinositol-3 kinase (PI3K)/AKT in sensitive cells inhibits c-Myc activation, which results in upregulation ofmiR-16. Forced expression of miR-16 inhibited in vitro proliferation in BC and GC cells, both sensitive and resistant to TZ andlapatinib, as well as in a preclinical BC model resistant to these agents. This reveals miR-16 role as tumor suppressor in ErbB-2-positive BC and GC. Using genome-wide expression studies and miRNA target prediction algorithms, we identified cyclin J and farupstream element-binding protein 1 (FUBP1) as novel miR-16 targets, which mediate miR-16 antiproliferative effects. Supportingthe clinical relevance of our results, we found that high levels of miR-16 and low or null FUBP1 expression correlate with TZresponse in ErbB-2-positive primary BCs. These findings highlight a potential role of miR-16 and FUBP1 as biomarkers of sensitivityto TZ therapy. Furthermore, we revealed miR-16 as an innovative therapeutic agent for TZ- and lapatinib-resistant ErbB-2-positiveBC and GC.